Structural Adjustment and Poverty Alleviation in the Philippines - Aniceto Jr. C. Orbeta (Philippine Institute for Development Studies (PIDS), 1996)
This paper reviews the Philippine structural adjustment and poverty alleviation experience. A review of the existing analyses of the impact of structural adjustment programs on poverty is given. To provide a background, a brief description of the development experience of the country and the poverty alleviation initiatives is also provided. Finally, lessons that can be drawn from the experience are presented.
Keywords: 330; poverty alleviation